Sludge Filtration Installation Design for Wastewater Treatment in Industrial Areas Using Bar Screens, Sedimentation, and Silica Sand Filtration Methods - Pita Rengga, Wara Dyah; Maulana, Dea; Widiastuti, Amelia Putri; Muna, Laili Nailil; Laksana, Mochamad Brian (Rekayasa, 2023)
Wastewater Treatment Plant is an important facility designed to process wastewater from various sources, such as households and industries, before it is discharged into the environment. The main purpose of WWTP is to eliminate or reduce contaminants in wastewater to meet the quality standards set by the government. The treatment process involves the screening stage of solid material, sludge sedimentation, and decomposition of biological or chemical contaminants. One of the main challenges in wastewater treatment is sludge carryover to the processing system, which can reduce pollutant parameters such as Biochemical Oxygen Demand, Chemical Oxygen Demand, Total Suspended Solids and ammonia. This study aims to design a sludge filtration system consisting of bar screening, sedimentation, and filtration unit with a combination of silica sand. The design is outlined in the form of a scientific article to contribute to the development of wastewater treatment studies. The bar screen is used to filter rough solids in the early stages, sedimentation is used to separate heavy particles using gravity, and the filtration unit is designed using a single silica sand filter to reduce TSS. With a processing discharge of 6,300 m³/day, the resulting design is expected to improve the operational performance of WWTPs, meet the wastewater quality standards according to PerMen LHK No. 16 of 2016, and produce good quality effluent BOD 13,43 mg/L, COD 40,47 mg/L, TSS 1,9 mg/L and ammonia 0,42 mg/L. The results of this planning provide a sustainable and efficient solution for wastewater treatment.